Physical and functional characterization of transcriptional control elements in the equine infectious anemia virus promoter. - Carvalho, M (1993)
Equine infectious anemia virus (EIAV) is a lentivirus that causes a chronic disease of horses characterized by cyclic episodes of fever, anemia, and viremia. Although the genome and promoter of EIAV are much less complex than those of its relatives the primate immunodeficiency viruses, the cellular proteins that activate and regulate transcription of EIAV have not yet been identified. In this report, we show by electrophoretic mobility shift assays and DNase I footprinting that the EIAV promoter contains multiple binding sites for ubiquitous, cell type-specific, and inducible cellular proteins. Functional analysis by transient transfection of canine osteosarcoma (D17) and human epithelial carcinoma (HeLa) cells with EIAV promoters containing deletions or individually mutated DNA-binding sites demonstrated that these DNA-binding elements cooperatively regulate transcriptional activity. A methylated DNA-binding site (MDBP; also designated EF-C or EP) acts as either a positive or negative regulator of promoter activity, depending on the cell type or condition. Two PEA2 elements, an AP-1 site, and an ets/PEA3 motif confer a positive effect on promoter activity. The EIAV promoter is shown to be activated by treatment of HeLa cells with phorbol myristate acetate (PMA). DNA-binding activities were induced in PMA-treated HeLa cells and formed complexes on oligonucleotides that contain the EIAV AP-1 and ets/PEA3 elements. Functional analysis of mutated promoters indicated that the ets/PEA3 motif was the principal mediator of PMA activation.